The impact of tourism mini-movies on destination image: The influence of travel motivation and advertising disclosure. Issue 3 (24th March 2017) - Gong, Tianyi; Tung, Vincent Wing Sun
ABSTRACT: Despite the growing use of mini-movies by tourism marketers, the effectiveness of this approach on inducing positive destination image remains relatively unexplored. This study examines the effectiveness of mini-movies in facilitating positive destination image while considering the influence of travel motivation and advertising disclosure via a 2 (travel motivation prime: presence versus absence) × 2 (advertising: disclosure versus non-disclosure) between-subjects experimental design. The methodology details the process of eliciting an individual's memorable tourism experience to prime future travel motivations. The study discusses implications for destinations that are looking to leverage the impact of mini-movies in their branding strategies. Abbreviations : DMO: destination marketing organization; SD: standard deviation; ANOVA: analysis of variance